The link between Gut Microbiota and Coronary Artery Disease (CAD) - A Review of literature - Adamczyk, Aleksandra; Ważny , Maria; Gancarz , Agnieszka; Żak , Agata; Gut , Michał; Toporowska-Kaźmierak, Joanna; Sowińska, Marta; Tworek , Miłosz; Banasik , Mateusz; Bezara , Damian (Quality in Sport, 2026)
Background: Coronary artery disease (CAD) is the leading cause of mortality worldwide. Although established risk factors such as hypertension or dyslipidaemia are well recognized, they do not fully account for the residual cardiovascular risk. Growing evidence suggest that the gut microbiota may play a significant role in development and progression of CAD through inflammatory, metabolic and immune-mediated mechanisms. Aim: This review aims to summarize current evidence on the association between the gut microbiome, its metabolites and CAD, and to discuss potential therapeutic strategies targeting the gut microbiota in CAD prevention and management. Materials and methods: The search was conducted using databases such as PubMed or Google Scholar. Following keywords were used: coronary artery disease, cardiovascular disease, gut microbiota, gut microbiome, dysbiosis, SCFAs, TMAO. Results: Patients with CAD exhibit gut microbiome dysbiosis, characterized by decrease of SCFA-producing bacteria and increase of microorganisms capable of TMAO synthesis. Decreased SCFAs production leads mainly to disrupted intestinal barrier integrity, resulting in leakage of pro-inflammatory LPS. On the other hand, TMAO has been strongly associated with CAD risk factors such as atherosclerosis. Emerging microbiota-targeted interventions like probiotics, prebiotics, symbiotics or fecal microbiota transplant have demonstrated promising results in the management of CAD. Conclusions: Gut microbiota represents an important and modifiable factor in the pathophysiology of CAD. At present, the dietary modifications offer the most accessible and effective strategy of microbiota modification and further research is needed to define the role of microbiome-related therapies.